Photoelectron spectra and angular distribution in sequential two-photon double ionization in the region of autoionizing resonances of ArII and KrII. (20th November 2020) - Kiselev, M D; Carpeggiani, P A; Gryzlova, E V; Burkov, S M; Reduzzi, M; Dubrouil, A; Faccialá, D; Negro, M; Ueda, K; Frassetto, F; Stienkemeier, F; Ovcharenko, Y; et al.
Abstract: Autoionizing hole states with electron configuration n s n p 5 m p are studied in Ar + and Kr + . Total and partial photoionization cross sections, photoelectron spectra and photoelectron angular distributions in the region of the resonances are obtained theoretically in extensive R -matrix calculations. The states of Ar + are observed by means of excitation by a free-electron laser operating in the vacuum- and extreme-ultraviolet wavelength regime combined with angle-resolved photoelectron spectroscopy. Fine tuning of the photon energy allows scanning of the resonances and the observation of the shape of the partial cross section ratio, as well as the asymmetry parameter of the angular distribution of the photoelectrons. The calculations are in good agreement with the experimental data.